Residents of Mainland play traditional Newfoundland music at a talent show at the "Vue de l’Ile" lounge - Tapp, Rose Marie (1990)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Report on a Field Trip to Mainland ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Report on a Field Trip to Mainland".